2017
DOI: 10.1080/00224499.2016.1271863
|View full text |Cite
|
Sign up to set email alerts
|

The Sexual Health of Transgender Men: A Scoping Review

Abstract: There is a general paucity of research concerning the sexual health of transgender individuals, and most existing research focuses on transgender women. A scoping review concerning the sexual health of transgender men was conducted to identify gaps in the literature and to highlight opportunities for future research and intervention. A comprehensive search of seven databases was conducted. The Joanna Briggs Institute Reviewers' Manual was used as a framework. Some 7,485 articles were initially identified using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
58
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(64 citation statements)
references
References 59 publications
2
58
0
2
Order By: Relevance
“…This was a convenience sample of trans MSM that is most likely not representative of the trans MSM population in its entirety. However, findings are generally consistent with existing HIV‐related studies in other high income settings . Respondents were recruited from a variety of sources, including social media, peer networks, and dating apps.…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…This was a convenience sample of trans MSM that is most likely not representative of the trans MSM population in its entirety. However, findings are generally consistent with existing HIV‐related studies in other high income settings . Respondents were recruited from a variety of sources, including social media, peer networks, and dating apps.…”
Section: Discussionsupporting
confidence: 74%
“…Higher perceived HIV risk was found to be associated with increased odds of PrEP indication among trans MSM. Prior research on perceived versus actual risk in trans MSM have been mixed, with some studies finding concordance and other others not . The congruency of high perceived risk and PrEP indications in this sample may be related to study eligibility criteria which was limited to trans MSM who had sex with cis man in the last six months.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…An important strength of this study is that most research thus far has only included transgender people with a diagnosis who are clinically referred or have already been treated (Klein & Gorzalka, 2009;Stephenson et al, 2017). In this way these studies focus on transgender people who seek genderaffirmation therapy.…”
Section: Factors Correlated With Sexual Behaviors and Feelingsmentioning
confidence: 99%
“…13,14 Similar to transgender women, transgender men are emotionally and sexually attracted to people of all gender identities and can identify as straight, gay, bisexual, queer, or with another sexual orientation, resulting in a range of sexual risk behaviors among this group. 15,16 One review found that a common goal of sexual behaviors among transgender men was affirmation of their post-transition masculinity, leading many to have receptive anal sex with cisgender men and avoidance of vaginal sex. 16 Infrequent condom use is also described among transgender men; in one study that included 62 transgender men, 71% reported not using a condom during their last sexual encounter.…”
Section: Introductionmentioning
confidence: 99%